MANAJEMEN PEMBELAJARAN MATEMATIKA METODE JIGSAWPADA SISWA SMK - Syalendra Putra (Manajer Pendididikan, 2016)
This study aims to find a mathematical learning management effective and efficient for students by enabling students active in learning. This research is the Classroom Action Research(CAR), which consists of several cycles and in each cycle includes planning, implementation, observation and reflection. The subjects were students of class X TB SMK Kota Bengkulu. From the results of the study saw an increase in student learning outcomes. In the first cycle of students can be increased by 20% from the initial conditions and the second cycle increased sebear 32%. From the results of this classroom action research, the researcher recommended to applymathematics learning management by Jigsaw method to improve learning outcomes and to enable the students active.Keywords: management, learning, mathematic, Jigsaw